THE MEANING AND VALUES OF LIFE DURING THE TRANSITION STAGE OF YOUTH FROM STUDIES TO WORK - POPOVICI Adriana (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Currently, the transition period from studies to work presents an essential and complex stage in the personal and professional evolution of young people, often characterized by challenges and uncertainties that affect their adaptability and long-term success. This process signifies the transition from the academic to the professional environment, involving experimentation and re-evaluation of meaning and values in life. The theoretical bases of the formation of orientations in life related to the meaning of existence as an important condition of life activity, are grounded in the works of philosophers, such as G. Hegel, I. Kant, E. Fromm, psychologists К. A. Abulkhanova-Slavskaya, B.S. Bratusy, A.Н. Leontiev, D.A. Leontiev, V.V. Stolin, V.E. Chudnovsky, the author of logotherapy V. Frankl. These scientific sources provide valuable information about the time period in which individuals navigate the complex process of identity formation, search for meaning, and adaptation of values. The purpose of this article is to investigate, both theoretically and practically, the meaning and value of life in this period of transition to adulthood from a psychological perspective. Emphasizing identity development, the search for meaning, and the adaptation of values. The importance of this subject lies in identifying the factors that contribute to the development of social maturity, in order to be able to develop effective strategies to support young people in this stage of life. In this context, the specialized literature emphasizes the fact that the meaning of life and values have a significant impact on the behavior and attitudes of young people, as well as on their career expectations.